THE CORRELATION BETWEEN SPIRITUAL INTELLIGENCE AND ACCESS TO PORNOGRAPHY WITH ADOLESCENT SEXUAL BEHAVIOR - Kadek Nela Ermira Prathiwi (UPT Penerbitan Universitas Jember, 2017)
Background: Adolescent sexual behavior is a risk factor that puts teenager in early adolescence period in unhealthy reproductive behaviors. Adolescent sexual behavior is influenced by various factors, such as hormonal changes, norms in society, dissemination of information through mass media, and spiritual intelligence. The aim of this study was to analyze the correlation, between spiritual intelligence and access to pornography with adolescent sexual behavior in Senior High School 1 Susut. Methods: This was a descriptive correlational study with cross-sectional design. The number of samples was 82 respondents which were collected by proportional random sampling. Data collection using questionnaires adopted from spiritual intelligence questionnaires and pornography access questionnaires. Results: The results showed that of respondents (58.5%) had high spiritual intelligence while most of the respondents (67.1%) seldom accessed pornographic content. Meanwhile, majority of respondents 62.2 % performed premarital sexual behavior with no risk. Conclusions: There was a significant correllation between spiritual intelligence and adolescent sexual behavior (p=0,00). There was also a significant correllation between access to pornography and adolescent sexual behavior (with p value of 0.00). The School can provide counseling or guidance about premarital sexual behavior of healthy. Keywords: spiritual intelligence, access to pornography, adolescent sexual behavior